Insulinotropic effect of Chikusetsu saponin IVa in diabetic rats and pancreatic β-cells. (22nd April 2015) - Cui, Jia; Xi, Miao-Miao; Li, Yu-Wen; Duan, Jia-Lin; Wang, Lei; Weng, Yan; Jia, Na; Cao, Shan-Shan; Li, Rui-Li; Wang, Chao; Zhao, Chao; Wu, Yin; et al.
Abstract: Ethnopharmacological relevance: As a well-known traditional Chinese medicine the root bark of Aralia taibaiensis has traditionally been used as the medicine considered alleviating several disorders including diabetes mellitus (DM). Chikusetsu saponin IVa (CHS) has been defined as a major active ingredient of triterpenoid saponins extracted from Aralia taibaiensis . The scientific evidence of anti-diabetic effect for CHS remains unknown and the purpose of our study was to study its hypoglycemic and insulin secretagogue activities. Materials and methods: In vivo studies were performed on type 2 diabetic mellitus (T2DM) rats given CHS for 28 days to test the antihyperglycemic activity. The in vitro effects and possible mechanisms of CHS on the insulin secretion in pancreatic β-cell line βTC3 were determined. Results: Oral administration of CHS dose-dependently increased the level of serum insulin and decreased the rise in blood glucose level in an in vivo treatment. In vitro, CHS potently stimulated the release of insulin from βTC3 cells at both basal and stimulatory glucose concentrations, the effect which was changed by the removal of extracellular Ca 2+ . Two methods showed that CHS enhanced the intracellular calcium levels in βTC3 cells. CHS was capable of enhancing the phosphorylation of extracellular signal-regulated protein kinases C (PKC), which could be reversed by a PKC inhibitor (RO320432), and the insulin secretion induced by CHS was also inhibited by RO320432. Further study also showed that the insulinotropic effect, intracellular calcium levels and the phosphorylation of PKC were reduced by inhibiting G protein-coupled receptor 40 (GPR40) by a GPR40 inhibitor (DC126026). Conclusion: These observations suggest that the signaling of CHS-induced insulin secretion from βTC3 cells via GPR40 mediated calcium and PKC pathways and thus CHS might be developed into a new potential for therapeutic agent used in T2DM patients. Graphical abstract: